Exploring the pathways: Regulatory experiments for Sustainable Development - An interdisciplinary approach - Dierk Bauknecht; Thore Bischoff; Kilian Bizer; Dirk Arne Heyen; Martin Führ; Peter Gailhofer; Till Proeger; Kaja von der Leyen (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
The Sustainable Development Goals (SDGs) adopted by the United Nations provide normative orientation for many national and regional governments as well as actors from industry and other parts of the civil society. There is growing consensus that the corresponding transformation processes needed - e.g. in the field of production and consumption patterns (SDG 12) - have to be fostered by a corresponding institutional framework. Properly designed regulatory experiments that generate a learning system for all actors involved may be an important building block. Based on an interdisciplinary approach, we develop an overview of the various terminologies for regulatory experimentation currently discussed in the social sciences, derive common criteria for regulatory experimentation in reflexive governance structures and conclude in presenting a conceptual framework for analysing empirical studies of regulatory experiments.
Keywords: L51; O31; Q58; 330; Regulation; Regulatory Experimenting; Sustainable Development; Reflexive Governance; Regulatory Learning